Misleading information about a product and antitrust law - Framiñán Santas, Javier (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
Dissemination of misleading information about a product can be considered a restriction of competition under certain conditions. This paper analyses what standard should be employed in the light of the EU Competition Law to evaluate such practice.